2021
DOI: 10.1021/acs.est.1c05901
|View full text |Cite
|
Sign up to set email alerts
|

Organic Coating Reduces Hygroscopic Growth of Phase-Separated Aerosol Particles

Abstract: A large fraction of secondary aerosol particles are liquid−liquid phase-separated with an organic shell and an inorganic core. This has the potential to regulate the hygroscopicity of such particles, with significant implications for their optical properties, reactivity, and lifetime. However, it is unclear how this phase separation affects the hygroscopic growth of the particles. Here, we showed a large variation in hygroscopic growth (e.g., 1.14−1.32 under a relative humidity (RH) of 90%) of particles from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…The other way is that aerosols can act as cloud condensation nuclei, affect the number density of cloud droplets and indirectly impact the climate. These impacts on climate substantially depend on the critical physicochemical properties of aerosols, including optical properties [1,2], heterogeneous chemistry [3,4], water uptake behavior [5,6], and nucleation activity [7][8][9][10]. These properties, in turn, are dictated by the morphology of the aerosols, especially the intern structure and phase state.…”
Section: Introductionmentioning
confidence: 99%
“…The other way is that aerosols can act as cloud condensation nuclei, affect the number density of cloud droplets and indirectly impact the climate. These impacts on climate substantially depend on the critical physicochemical properties of aerosols, including optical properties [1,2], heterogeneous chemistry [3,4], water uptake behavior [5,6], and nucleation activity [7][8][9][10]. These properties, in turn, are dictated by the morphology of the aerosols, especially the intern structure and phase state.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed this wide range to variations in the thickness of the organic shell on the phase-separated particles; measurements on lab-generated aerosol particles support this conclusion. 232 Therefore, because water uptake depends so strongly on surface morphology, ensemble averages for hygroscopic growth factors and κ are not meaningful for externally mixed populations of ambient aerosol particles.…”
Section: Cloud Droplet Activationmentioning
confidence: 99%
“…3,[225][226][227] Indeed, water uptake by aerosol particles is highly dependent on phase and mixing state. [228][229][230][231][232] In a relatively simple system of fatty acids on sea salt particles, Nguyen et al 233 found that palmitoleic acid (C16) and oleic acid (C18), which are liquids at room temperature, did not impede water uptake, whereas the analogous saturated fatty acids, palmitic acid (C16) and stearic acid (C18), which are solids at room temperature, did hinder water uptake. The authors attribute the opposing effects to phase.…”
Section: Hygroscopicitymentioning
confidence: 99%
“…In addition, it should be noted that the hygroscopicity is not only determined by the bulk composition; it is also affected by the phase state of the particles. For instance, a recent study revealed that the hygroscopic growth of phase-separated particles (with ammonium sulfate cores) can be reduced by secondary organic shells and is dependent on the thickness of the organic coating (Li et al, 2021).…”
Section: Size-resolved Hygroscopicity Of Rbcc Particlesmentioning
confidence: 99%
“…Refractory black carbon (rBC) aerosols can directly absorb solar radiation, indirectly change the nature of clouds and alter the albedo of snow or glaciers (Jacobi et al, 2015), resulting in a positive radiative forcing that is second only to carbon dioxide at both regional and global scales (Ramanathan and Carmichael, 2008;Bond et al, 2013). The fresh rBC particles produced by incomplete combustion of biomass and fossil fuel tend to be fractal in morphology and can mix with many other components (Peng et al, 2016;Li et al, 2021). After entering into the atmosphere, fresh rBC can further mix externally or internally with organic/inorganic species that have undergone primary emission or are formed secondarily, and such aged rBC-containing (rBCc) particles (Chen et al, 2017;Lee et al, 2017) may have contrasting chemical properties and morphologies (or mixing states) (D. Lee et al, 2019;Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%